Pembinaan Majelis Kehormatan Notaris Dan Majelis Pengawas Notaris Berdasarkan Undang-Undang Jabatan Notaris - S. Rijal Khalis (Universitas Islam Indonesia, 2021)
The purpose of this study is to find out and examine the differences in the development of the Notary Honorary Council (MKN) and the Notary Supervisory Council (MPN) as well as the implementation of guidance by the Notary Honorary Council and Notary Supervisory Council in Yogyakarta City to the Notary. This research is normative with statutory and conceptual approaches. The results of the study concluded that first, MKN and MPN in providing guidance to Notaries in the City of Yogyakarta have the similar mentoring authority and differences, MKN only provides guidance in the task of implementing Notaries. Meanwhile, MPN provides guidance in the implementation of Notary duties, the Notary Code of Ethics, and the behavior of Notaries outside the Notary's office. Second, the guidance carried out by both MKN and MPN to Notaries is still not perfect because it is still unclear what authority is given by the legislation in terms of how the guidance should be carried out by MPN and MKN as well as the boundaries between the two bodies in conducting coaching.Key Words: Mentoring; notary honorary assembly; notary supervisory boardAbstrakTujuan penelitian ini untuk mengetahui dan mengkaji perbedaan pembinaan Majelis Kehormatan Notaris (MKN) dan Majelis Pengawas Notaris (MPN) serta implementasi pembinaan oleh Majelis Kehormatan Notaris dan Majelis Pengawas Notaris di Kota Yogyakarta kepada Notaris. Penelitian ini bersifat normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian menyimpulkan bahwa pertama, MKN dan MPN dalam melakukan pembinaan terhadap Notaris di Kota Yogyakarta memiliki kesamaan kewenangan pembinaan dan perbedaan, MKN hanya melakukan pembinaan dalam tugas pelaksanaan Notaris. Sedangkan MPN melakukan pembinaan dalam tugas pelaksanaan Notaris, Kode Etik Notaris, dan prilaku Notaris di luar jabatan Notaris. Kedua, pembinaan yang dilakukan MKN dan MPN terhadap Notaris masih belum sempurna karena masih belum jelas kewenangan yang diberikan oleh peraturan perundang-undangan dalam hal bagaimana seharusnya pembinaan yang harus dilakukan dilakukan MPN dan MKN serta batasan-batasan di antara kedua badan tersebut dalam melakukan pembinaan.Kata Kunci: Pembinaan; majelis kehormatan notaris; majelis pengawas notaris